Absence of antibodies to Rickettsia spp., Bartonella spp., Ehrlichia spp. and Coxiella burnetii in Tahiti, French Polynesia - Musso, Didier (BioMed Central, 2014)
ABTRACT: BACKGROUND: In the Pacific islands countries and territories, very little is known about the incidence of infectious diseases due to zoonotic pathogens. To our knowledge, human infections due to Rickettsia spp., Coxiella burnetii, Ehrlichia spp. and Bartonella spp. have never been reported in French Polynesia; and infections due to C. burnetti have been reported worldwide except in New Zealand. To evaluate the prevalence of this disease, we conducted a serosurvey among French Polynesian blood donors. METHODS: The presence of immunoglobulin G antibodies against R. felis, R. typhi, R. conorii, C. burnetii, B. henselae, B. quintana, and E. chaffeensis was evaluated by indirect immunofluorescence assay in sera from 472 French Polynesian blood donors collected from 2011 to 2013. In addition, 178 ticks and 36 cat fleas collected in French Polynesia were also collected and tested by polymerase chain reaction to detect Rickettsia spp., B. henselae and Ehrlichia spp. RESULTS: None of the blood donors had antibodies at a significant level against Rickettsia spp., Coxiella burnetii, Ehrlichia spp. and Bartonella spp. All tested ticks and cat fleas were PCR-negative for Rickettsia spp., B. henselae, and Ehrlichia spp. CONCLUSION: We cannot conclude that these pathogens are absent in French Polynesia but, if present, their prevalence is probably very low. C. burnetii has been reported worldwide except in New Zealand. It may also be absent from French Polynesia.